2007
DOI: 10.1177/1066896907302119
|View full text |Cite
|
Sign up to set email alerts
|

Colonic Aberrant Crypts in Children With Familial Adenomatous Polyposis

Abstract: Aberrant crypt foci of the colonic mucosa have been reported in adults. The alteration may be defined macroscopically or histologically and may or may not be combined with adenomatous changes. Aberrant crypt foci have been regarded as precancerous lesions and are more common in patients with familial adenomatous polyposis. The present report describes the presence of many histologically recognizable aberrant crypt foci without adenomatous changes in the colonic mucosa of 3 children with familial adenomatous po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The nuclei of some epithelial cells are enlarged. It has been found that epithelial cells from aberrant crypts have gene mutations, which are the earliest stage of cancer progression [89]. Stromal cells are also altered [90].…”
Section: Epigenetic Influence Of Activated Stroma Triggers Malignant mentioning
confidence: 99%
“…The nuclei of some epithelial cells are enlarged. It has been found that epithelial cells from aberrant crypts have gene mutations, which are the earliest stage of cancer progression [89]. Stromal cells are also altered [90].…”
Section: Epigenetic Influence Of Activated Stroma Triggers Malignant mentioning
confidence: 99%